INTERVENSI KONSELING KARIR BERFOKUS SOLUSI TERHADAP PENINGKATAN SELF-EFFICACY SISWA SEKOLAH MENENGAH ATAS SAMARINDA - nurlianawati, selvy; Widyatmoko, Wahyu (IKIP Siliwangi, 2025)
Self-efficacy is an individual's belief in their ability to face challenges and complete certain tasks. Based on the results of the pre-study, it shows low student self-efficacy, which is in accordance with the results of AKPD, observations, and interviews with BK teachers. This study aims to prove solution-focused career counseling services as an intervention in improving the self-efficacy of Samarinda high school students. This study uses an experimental research method with a one-group pre-test and post-test design and a quantitative approach. The determination of the subjects of this study used non-probability sampling with a purposive sampling technique of 9 students. The solution-focused career counseling service intervention was carried out in 7 meetings. The results of this study showed an increase in student self-efficacy, namely an average pre-test score of 74.8 and an average post-test score of 104.5. The results of data analysis showed that the sig. value in the pre-test was 0.054> 0.05 and the post-test was 0.761> 0.05. Thus, it can be concluded that the data is normally distributed. The results of the paired sample t test obtained a significance value (2-tailed) = 0.001 < 0.005. So it can be concluded that solution-focused career counseling can be applied to improve the self-efficacy of high school students in Samarinda.